2004
DOI: 10.1191/0960327104ht454oa
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological features of deliberate self-poisonings

Abstract: Background: Deliberate self-poisoning (DSP) is a major health problem with increasing incidence mainly among young people. Objective: To examine the clinical and toxicological characteristics of DSP, it is compared to unintentional (non-DSP) exposures and those characteristics which might be associated with increased toxicological risk are identified. Methods: Two-year retrospective poison centre chart review. Statistics: χ2 analysis. Results: 3802 DSP cases were reported. Most ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
(8 reference statements)
1
15
0
2
Order By: Relevance
“…This unanticipated finding was attributed to the increased proportion of newer, less toxic antidepressants [30]. All in all, our results confirm that the newer antidepressants are much safer than other common drugs involved in fatal intoxications, and the differences in toxicity between the newer antidepressants are small.…”
Section: Drug Safetysupporting
confidence: 79%
“…This unanticipated finding was attributed to the increased proportion of newer, less toxic antidepressants [30]. All in all, our results confirm that the newer antidepressants are much safer than other common drugs involved in fatal intoxications, and the differences in toxicity between the newer antidepressants are small.…”
Section: Drug Safetysupporting
confidence: 79%
“…This often leads to poisoning. Therefore, the poisonings during the period of adolescence represent the major problem, and the frequency is the highest in childhood and adolescence and in the preschool age in Serbia (from 2 to 7 years) (Bronstein et al, 2008;Iancu et al, 1997;Ulmeanu & Niteskcu Girnia, 2005;Bentur et al, 2008;Lifshitz & Gavrilov, 2000;Mintegi et al, 2006;Martins, de Andrade, & de Paiva, 2006;Von Mach, Habermehl, Zepp, & Weilemann, 2006;Shotar, 2005;Matteucci, 2005;Szkolnicka, Mitrus, Morawska, Satora, & Targosz, 2005;Boyanova, Loukova, Stankova, & Hubenova, 2005;Hon et al, 2005;Bentur et al, 2004). Most of our patients reported that they used alcohol and=or drugs, mostly anxiolytics, before the actual poisoning (which was the cause of the admission to the Emergency Centre).…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo sobre hospitalização nas tentativas de suicídio e suicídio, Iribarren et al 28 constataram uma maior incidência entre os que usaram, como método, a ingestão de medicamentos psicotrópicos e armas de fogo, respectivamente, destacando-se o sexo feminino no primeiro grupo. Analisando apenas as hospitalizações devido a tentativas de suicídio por auto-intoxicação, Bentur et al 29 verificaram que o uso de diferentes tipos de substâncias medicamentosas correspondia a 38% dos casos, sendo encontrada uma porcentagem de 42,2% nesse estudo.…”
Section: Discussionunclassified
“…Como neste estudo foi definida a faixa etária de 20-40 anos, por ser a faixa na qual ocorre mais freqüentemente intoxicação voluntária por medicamentos segundo dados do SINITOX, não foi possível constatar diferença entre os medicamentos utilizados por indiví-duos mais jovens e mais velhos. Vários estudos mostram que os mais jovens fazem maior uso de analgésicos e outros medicamentos de venda livre, e indivíduos mais velhos, de psicofárma-cos 8,22,29 .…”
Section: Discussionunclassified